2019
DOI: 10.1038/s41598-019-44479-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the WRKY gene family in cultivated strawberry (Fragaria × ananassa Duch.) and the importance of several group III members in continuous cropping

Abstract: WRKY transcription factors play important roles in many plant developmental processes and adaptation to the environment. However, little knowledge is available about the WRKY gene family in cultivated strawberry ( Fragaria × ananassa Duch.), an important soft fruit worldwide. In this study, a total of 47 WRKY gene members were identified and renamed on the basis of their order on the chromosomes. According to their evolutionary events and conserved structure, the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Particularly, we highlighted the presence of two types of core responsive genes that were regulated at both levels by at least four stresses, the WRKY family of genes and genes encoding heat shock proteins (HSPs). WRKY transcription factor genes, known as the largest gene family in higher plants, have been reported in many species including Arabidopsis , rice, tomato, cotton, pineapple and wild strawberry [ 39 ]. Massive studies have indicated the regulatory role of WRKY gene members that confers biotic as well as abiotic stress tolerance to crop plants [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we highlighted the presence of two types of core responsive genes that were regulated at both levels by at least four stresses, the WRKY family of genes and genes encoding heat shock proteins (HSPs). WRKY transcription factor genes, known as the largest gene family in higher plants, have been reported in many species including Arabidopsis , rice, tomato, cotton, pineapple and wild strawberry [ 39 ]. Massive studies have indicated the regulatory role of WRKY gene members that confers biotic as well as abiotic stress tolerance to crop plants [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The members of group III consist of a WRKY domain and C2H2 zinc-finger sequence (Jang et al, 2010;Zhu et al, 2013). A large number of studies have reported useful information on WRKY gene family in a number of species like rice, tomato, cotton, Arabidopsis, pineapple and strawberry (Chen and Liu, 2019). To the best of our knowledge little is investigated regarding the structural and functional analysis of WRKY genes found in various cereal crops.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found some differentially expressed miRNAs involved in the development of the tuberous root after a R. glutinosa CC obstacle [17]. In our previous study, we found that several WRKY group III members might play important roles in the response to CC obstacles in strawberry [18]. However, no report is available regarding the recovery strategies in plant roots after application of the SA to CC soil.…”
Section: Introductionmentioning
confidence: 85%